Experimental Build of a Two-Wheeled Inverted Pendulum Mobile Robot - Kohlbrecher, Blake; Antoun, Sherine (European Journal of Applied Sciences, 2023)
This undergraduate research project describes the construction, autonomous control, and exploration of potential uses of a Two-Wheeled Inverted Pendulum (TWIP) in uncontrolled environments [1]. Initially, the non-functioning physical design is two repurposed wheelchair wheels and motors mounted to a chassis that holds two batteries to power the robot. The goal was to continue with the legacy design, augment the build to the point where the robot is programmable, and potentially add sensors for further applications. Another goal was to learn how to design a safe circuit to power the robot and its controllers. Another objective was to learn about the fundamentals of programming an autonomous robot. This paper describes the experimental research progress and findings. The robot is currently programmable with an Arduino Mega 2560, which controls the wheels with two separate motor controllers. It has a limited footprint and has the potential to carry substantial payloads, which promises to be beneficial in uncontrolled workspaces. The initial research has the robot capable of being programmed to go in a straight line and currently has an MPU 6050 accelerometer and gyro attached to the Arduino, delivers state data used to make accurate turns and sense whether the robot has accelerated too quickly and may be in danger of becoming unbalanced.